(untitled) (The Review of Diabetic Studies, 2025)
Background: Saudi Arabia’s healthcare system is undergoing significant reforms under Vision 2030, which has led to an expansion of nursing roles and responsibilities. As the country addresses the growing demand for specialized care, there is an increasing need for Advanced Practice Nurses (APNs), Nurse Practitioners (NPs), and telehealth nurses. However, despite the growing demand, these emerging nursing roles face several challenges, including regulatory barriers, role ambiguity, and insufficient training programs. Aim: This systematic review aims to explore and synthesize the evidence on emerging nursing roles in Saudi Arabia, focusing on their responsibilities, requirements, and the challenges to their integration into the healthcare system. Method: A comprehensive search of PubMed, CINAHL, Scopus, Web of Science, and Google Scholar was conducted to identify studies published between 2021 and 2025. Studies included in the review focused on nursing roles such as APNs, NPs, and telehealth nurses in Saudi Arabia. A thematic synthesis of the data was performed, and studies were assessed for quality using appropriate appraisal tools. Results: The review identified that emerging nursing roles are essential for addressing healthcare demands, particularly in chronic disease management and rural healthcare. Barriers to role integration, including regulatory gaps and cultural resistance, were common across studies. The need for specialized training programs and role clarity was emphasized to facilitate successful integration. Conclusion: Emerging nursing roles in Saudi Arabia hold significant potential to enhance healthcare delivery. However, policy reform, role definition, and training initiatives are needed to fully integrate these roles into the healthcare system.